A New Design of MP-HDCCB Topology Based on Hybrid Switching Device - Haipeng Jia; Jingyuan Yin; Tongzhen Wei; Jinke Li; Jin Zhu; Zeyu Ye (Energies, 2022)
Since each branch of the multiterminal DC circuit system relies on the DC circuit breaker for breaking and fault isolation, the prohibitive cost and huge volume of the Hybrid DC Circuit Breaker (HCB) limit its development and broad application in multiterminal flexible DC systems. Multiport hybrid DC circuit breaker (MP-HDCCB) based on device and branch sharing reduces the configuration cost of the circuit breaker to a certain extent. In order to further reduce the cost of MP-HDCCB, a novel MP-HDCCB topology based on hybrid switching devices is proposed, adopting full controlled switching devices to achieve rapidity of breaking fault current, and using semi-controlled switching devices in series to withstand the transient interruption voltage (TIV), so as to reduce the construction cost and technical difficulty. In this paper, the working principle and fault breaking strategy of the topology are introduced in detail, then the parameters of the major circuit are analyzed theoretically, and the parameter design of each branch is given. In the end, the rationality and validity of the proposed topology is tested and verified by simulations and experimental tests.